Both life‐history plasticity and local adaptation will shape range‐wide responses to climate warming in the tundra plant Silene acaulis. (12th December 2017) - Peterson, Megan L.; Doak, Daniel F.; Morris, William F.
Abstract: Many predictions of how climate change will impact biodiversity have focused on range shifts using species‐wide climate tolerances, an approach that ignores the demographic mechanisms that enable species to attain broad geographic distributions. But these mechanisms matter, as responses to climate change could fundamentally differ depending on the contributions of life‐history plasticity vs. local adaptation to species‐wide climate tolerances. In particular, if local adaptation to climate is strong, populations across a species' range—not only those at the trailing range edge—could decline sharply with global climate change. Indeed, faster rates of climate change in many high latitude regions could combine with local adaptation to generate sharper declines well away from trailing edges. Combining 15 years of demographic data from field populations across North America with growth chamber warming experiments, we show that growth and survival in a widespread tundra plant show compensatory responses to warming throughout the species' latitudinal range, buffering overall performance across a range of temperatures. However, populations also differ in their temperature responses, consistent with adaptation to local climate, especially growing season temperature. In particular, warming begins to negatively impact plant growth at cooler temperatures for plants from colder, northern populations than for those from warmer, southern populations, both in the field and in growth chambers. Furthermore, the individuals and maternal families with the fastest growth also have the lowest water use efficiency at all temperatures, suggesting that a trade‐off between growth and water use efficiency could further constrain responses to forecasted warming and drying. Taken together, these results suggest that populations throughout species' ranges could be at risk of decline with continued climate change, and that the focus on trailing edge populations risks overlooking the largest potential impacts of climate change on species' abundance and distribution. Abstract : Predictions of climate change impacts largely focus on species' responses at range edges, assuming this is where climate change will first exceed species‐wide climate tolerances, and thus most strongly impact populations. Combining 15 years of field observations with warming experiments, we show that temperature responses in growth and survival differ across the latitudinal range of the tundra plant Silene acaulis, with performance declining at lower temperatures in northern populations. Widespread species may not respond to climate change by "rolling back" the warm‐edge, as many models have assumed, but instead decline throughout their ranges as climate change exceeds local tolerances.